I'm Too Busy - Helen Stephens 1972- (UK Dorling Kindersley, 1998)
Charlie the cat is so busy directing traffic and lifting weights, and other things, he doesn't have time to eat his supper.
Keywords: General -- Fiction; Cats; Toddler Proof